Number of blades of rotating blades affecting the boiling heat transfer enhancement of distilled water - A Suriyawong; S Saisorn; A Kawahara; S Wongwises (My University, 2019)
This study examined the nucleate pool boiling characteristics of distilled water attached to a heating surface with a horizontal circular plate above which the rotating blades were installed. The experiments were performed to explore the effects of number of blades as well as the visualization of pool boiling phenomena on nucleate boiling heat transfer characteristics. The rotating blades were made from copper material, with the number of blade of 2, 3 and 4 blades. The results showed that, the rotor with 4 blades yielded a higher heat transfer coefficient than those with 2 or 3 blades. This is because the increased number of blade provided more chance for the bubbles to strike the rotating blades. Hence, the rotating blades did create a commotion of the working fluid above the heating surface. Camera frames were captured using an Aos Promon Studio at the heat fluxes of about 160-610 kW/m2 to identify the location of bubble nucleation for each configuration. The photographic observations showed that, the pool boiling phenomenon with the heat flux value of about 160 kW/m2 corresponded to the isolated bubble, and the boiling characteristic with the heat flux value of about 610 kW/m2 were based on the column regime.
Keywords: Distilled water; Heat Transfer and Boiling Studies